2014
DOI: 10.1111/1753-0407.12210
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of oil's fatty acids on T cell function in gestational diabetic pregnant women and their newborns 油类脂肪酸在体外对妊娠期糖尿病孕妇及其新生儿的T细胞功能的影响

Abstract: Linseed, olive and Nigel oils had beneficial effects on T cell functions in gestational diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 45 publications
(131 reference statements)
1
8
0
Order By: Relevance
“…We observed that in the presence of linseed and Nigel oils, the T cell oxidant markers, MDA and carbonyl proteins were reduced in obese patients, probably as a consequence of enhanced antioxidant defense. These results are in agreement with previous reports on antioxidant effects of linseed and Nigel oils [21].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…We observed that in the presence of linseed and Nigel oils, the T cell oxidant markers, MDA and carbonyl proteins were reduced in obese patients, probably as a consequence of enhanced antioxidant defense. These results are in agreement with previous reports on antioxidant effects of linseed and Nigel oils [21].…”
Section: Discussionsupporting
confidence: 94%
“…Dietary n-3 PUFAs promote apoptosis in a T cell subset exhibiting a Th1 cytokine profile, affecting T cell proinflammatory function [19]. N-3 PUFA improved T cell intracellular oxidative status in diabetes and in gestational diabetes [20] [21]. α-linolenic acid (ALA, C18:3 n-3) is an important n-3 PUFA supplied by vegetable sources such as linseed oil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of those two, OA is the most abundant form of a monounsaturated omega-9 fatty acid (C18:1 cis-9) that is produced by stearoyl CoA desaturase 1 (SCD1), mainly from stearic acid (C18:0) by catalyzing Δ9 desaturation [5]. Moreover, OA has been recognized as an effective biomolecule because it causes MSCs to secrete angiogenic mediators and regulates immunomodulatory functions [4,6,7]. Though the significance of OA with regard to the modulation of stem cell functions has been recognized, the mechanism by which OA mediates beneficial physiological effects at the intracellular signaling level has not been completely described.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to our findings, Zhao & Wang (34) found that n-3 fatty acids applied as a part of parenteral nutrition in postoperative patients with gastrointestinal malignancy decreased CRP and other inflammatory markers. An in vitro study demonstrated that peripheral blood lymphocytes of women with GDM when exposed to n-3 fatty acids caused elevated GSH and decreased MDA cell levels (35) . A 12-week n-3 fatty acid supplementation with 2 g/d flaxseed oil improved hs-CRP and GSH levels in patients with grade 3 diabetic foot ulcer (36) .…”
Section: Effects On Biomarkers Of Inflammation and Oxidative Stressmentioning
confidence: 99%